Prevalence and factors associated with mild depressive and anxiety symptoms in older adults living with HIV from the Kenyan coast - Mwangala, PN; Nasambu, C; Wagner, RG; Newton, CR; Abubakar, A (Wiley, 2022)
Introduction Empirical research on the burden and determinants of common mental disorders (CMDs), especially depression and anxiety, among older adults living with HIV (OALWH) in sub-Saharan Africa is inadequate. To bridge the gap in Kenya we: (1) determined the prevalence of CMDs among OALWH on routine HIV care compared to HIV-negative peers; (2) investigated HIV status as an independent predictor of CMDs in older adults; and (3) investigated CMD determinants.